Chronic Anal Fissure: A Literature Review - Wulandari, Baiq Nurhandini; Mikailla, Romy Healthy; Wardana, Shira Putri; Aisyah S.F., Nadine; Sena R., Panji; Aghni, Hasna Tazkia; Nurhidayati, Nurhidayati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Chronic anal fissure is a common anorectal condition characterized by persistent mucosal tears that cause severe pain and reduced quality of life. Effective management is essential, as many cases show poor response to conservative treatment. This study aims to review recent advances in the diagnosis and management of chronic anal fissure. A literature review was conducted through PubMed, Google Scholar, and ProQuest using the keywords “Chronic Anal Fissure OR Persistent Anal Fissure,” applying inclusion and exclusion criteria to ensure relevance and scientific quality. The findings indicate that conservative therapy achieves healing in only about 50% of patients, while others require pharmacological or surgical interventions. Newer modalities, including topical calcium channel blockers, botulinum toxin injections, and modified surgical techniques such as anal advancement flap, demonstrate higher success rates with fewer complications. Furthermore, multitarget topical formulations have recently emerged as promising therapeutic options. In conclusion, the management of chronic anal fissure is evolving toward more effective and safer strategies. Further research is recommended to validate multitarget therapies and to develop individualized treatment approaches that improve patient outcomes and long-term quality of life.